2022
DOI: 10.1002/adsc.202200716
|View full text |Cite
|
Sign up to set email alerts
|

Radical C−H Alkylation with Ethers and Unactivated Cycloalkanes toward the Assembly of Tetrasubstituted Amino Acid Derivatives

Abstract: A radical α−C−H alkylation of a collection of N‐picolinamide amino acid derivatives with ethers and cycloalkanes as chemical feedstock is described. This cross‐dehydrogenative coupling is distinguished by its reliable scalability and removable auxiliary group, and enables the assembly of a variety of tri‐ and tetrasubstituted amino acid compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Recently, we disclosed our pioneering findings on iron and nickel-catalyzed CDC reaction of α-tertiary α-AAs with different coupling partners for the preparation of diverse of α-(hetero)aryl-α-alkyl and α,α-dialkyl α-AA scaffolds with the assistance of 2-picolinamide as an efficient auxiliary . Inspired by our strategy, Correa’s group showed that ethers and cycloalkanes were suitable reaction partners and gained access to tri- and tetrasubstituted α-AA derivatives . More recently, Yazaki and Ohshima developed an efficient copper-catalyzed CDC process between α-AA Schiff bases and hydrocarbon feedstocks for the synthesis of sterically hindered α,β-tetrasubstituted α-AA precursors .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we disclosed our pioneering findings on iron and nickel-catalyzed CDC reaction of α-tertiary α-AAs with different coupling partners for the preparation of diverse of α-(hetero)aryl-α-alkyl and α,α-dialkyl α-AA scaffolds with the assistance of 2-picolinamide as an efficient auxiliary . Inspired by our strategy, Correa’s group showed that ethers and cycloalkanes were suitable reaction partners and gained access to tri- and tetrasubstituted α-AA derivatives . More recently, Yazaki and Ohshima developed an efficient copper-catalyzed CDC process between α-AA Schiff bases and hydrocarbon feedstocks for the synthesis of sterically hindered α,β-tetrasubstituted α-AA precursors .…”
mentioning
confidence: 99%
“…Based on the above observations and previous reports, ,, the plausible mechanism for this CDC process is proposed in Scheme c. Initially, the 2-picolinamide substrate acts as a ligand to coordinate with Cu(II) to generate intermediate IM1 .…”
mentioning
confidence: 99%
See 1 more Smart Citation